An Optimization Framework for an Integrated and Sustainable Coconut Processing System - Anwar, Syamsul; Meilizar, M; Harif, Muhammad (Universitas Muhammadiyah Surakarta, 2025)
Coconut agro-industries in tropical regions, including Indonesia, play a critical role in rural economies but often face challenges related to low resource efficiency, fragmented processing systems, and the underutilization of by-products. These inefficiencies lead to economic losses and environmental burdens due to biomass waste. This study aims to develop an integrated and sustainable optimization framework for coconut processing that simultaneously enhances profitability and ensures the full utilization of coconut biomass. The framework is formulated as a Mixed-Integer Linear Programming (MILP) model that captures production interdependencies, raw material constraints, and facility capacity limitations across multiple processing units, including oil extraction from coconut fruits, charcoal production from coconut shells, and flour processing from coconut pulp. The model implementation demonstrates the viability of integrated production planning, with optimal facility activation and complete utilization of coconut derivatives, in line with circular economy principles. These findings highlight the potential of the proposed model as a robust decision-support tool for improving sustainability and efficiency in coconut-based agro-industry.